Usefulness of an early neurofunctional assessment in predicting neurodevelopmental outcome in very low birthweight infants. Issue 2 (21st February 2006) - Picciolini, O; Giannì, M L; Vegni, C; Fumagalli, M; Mosca, F
Abstract : Objective: To evaluate whether early neurofunctional assessment may be useful in predicting neurodevelopmental outcome in children of very low birth weight (VLBW). Design: Observational longitudinal study. Settings: Northern Italy. Patients: A total of 250 VLBW children (129 boys, 121 girls) born consecutively 1996–1999. Main outcome measures: Neurodevelopment at 36 months of chronological age, classified in accordance with the classification of Tardieu and the International classification of functioning . Results: Of the infants exhibiting normal neurodevelopment (n  =  183) or major dysfunction (n  =  17) at 3 months of corrected age, 72% and 94% respectively did not change their score during the study. Minor dysfunctions at 3 months of corrected age were transient in 17 (34%) children. After adjustment for neonatal variables, neurodevelopment at 3 months of corrected age remained predictive of dysfunction at 36 months (odds ratio  =  4.33, 95% confidence interval 2.05 to 9.12). If the results for the normal and minor dysfunction groups were pooled, the predictive qualities of the 3 month neurofunctional assessment were: sensitivity 0.5, specificity 0.99, positive predictive value 0.94, negative predictive value 0.93. Conclusion: Early neurofunctional evaluation may be useful in predicting later neurodevelopmental outcome in VLBW children.